2011
DOI: 10.1007/s10875-010-9495-1
|View full text |Cite
|
Sign up to set email alerts
|

Neural System Antigens Are Recognized by Autoantibodies from Patients Affected by a New Variant of Endemic Pemphigus Foliaceus in Colombia

Abstract: Background Endemic pemphigus foliaceus (EPF), is also known as “fogo selvagem” or “wild fire,” reflecting the intense burning sensation of the skin reported by patients with this disease. Based on this finding, we tested for neural autoreactivity in patients affected by a new variant of EPF (El Bagre-EPF). Methods We tested 20 El Bagre-EPF patients, 20 normal controls from the endemic area, and 20 age- and sex-matched normal controls from outside the endemic area. We tested for autoreactivity to several immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…We also utilized 15 control skin biopsies from cosmetic surgery patients in the USA, taken from the chest and/or abdomen. The Bagre-EPF patients were previously diagnosed by us, fulfilling specific criteria as previously documented [6][7][8][9][10]. We also tested another group of ABD patients, whose skin biopsies were obtained from the archival files of two private dermatopathology laboratories in the USA.…”
Section: Subjects Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We also utilized 15 control skin biopsies from cosmetic surgery patients in the USA, taken from the chest and/or abdomen. The Bagre-EPF patients were previously diagnosed by us, fulfilling specific criteria as previously documented [6][7][8][9][10]. We also tested another group of ABD patients, whose skin biopsies were obtained from the archival files of two private dermatopathology laboratories in the USA.…”
Section: Subjects Of Studymentioning
confidence: 99%
“…The organs from the autopsies were taken within 12 hours of patient death. The direct immunofluoresecent studies (DIF) were performed as previously described [6][7][8][9][10].…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested 30 biopsies from patients affected by endemic pemphigus foliaceus in El Bagre, Colombia (El Bagre-EPF); diagnostic criteria were followed as previously described [8][9][10]. We also tested skin biopsies from 30 controls from the El Bagre EPF endemic area, and 30 additional control skin samples from cosmetic surgery patients in the USA, taken from the chest and/or abdomen.…”
Section: Subjects Of Studymentioning
confidence: 99%
“…Our H & E staining and IHC studies were performed as previously reported [56][57][58][59][60]. For IHC, we utilized the following antibodies: monoclonal mouse anti-human TTF-1, insulin-like growth factor II mRNA binding protein 3 (IMP3), ribosomal protein S6-pS240/phosphorylation site specific, serotonin, survivin, synaptophysin, bromodeoxyuridine, tissue inhibitor of metalloproteinases 1 (TIMP-1), CK20, NSE, neurofilament protein, cyclo-oxygenase enzyme 2 (COX-2), Cyclin D1, CD56/NCAM, Chromogranin A (CgA), calretinin, epithelial membrane antigen (EMA/CD227), Ber-EP4, pancytokeratin (clone AE1/AE3), proliferating cell nuclear antigen (PCNA), MIC2 and Ewing's sarcoma marker (CD99).…”
Section: Methodsmentioning
confidence: 99%